Multiple Eruptive Dermatofibromas in a Patient with HIV infection - Miroux Catarino, Alexandre (2018)
Multiple eruptive dermatofibromas is a rare event characterized by the appearance multiple dermatofibromas in few months. It is usually associated with immunodysregulation/immunosuppression. An appropriate work-up of underlying diseases must be done after this diagnosis, including search for HIV infection and lupus erythematosus. We present a case of multiple eruptive dermatofibromas in a female patient with HIV infection, possibly associated with a decrease in the CD4+ T cell count and viral load increase.